Asymmetric hydrogenation for the synthesis of 2-substituted chiral morpholines. Issue 45 (8th November 2021) - Li, Mingxu; Zhang, Jian; Zou, Yashi; Zhou, Fengfan; Zhang, Zhenfeng; Zhang, Wanbin
Abstract : 2-Substituted chiral morpholines were synthesized via a newly developed asymmetric hydrogenation of dehydromorpholines catalyzed by a bisphosphine–rhodium complex bearing a large bite angle. Abstract : Asymmetric hydrogenation of unsaturated morpholines has been developed by using a bisphosphine-rhodium catalyst bearing a large bite angle. With this approach, a variety of 2-substituted chiral morpholines could be obtained in quantitative yields and with excellent enantioselectivities (up to 99% ee). The hydrogenated products could be transformed into key intermediates for bioactive compounds.